Internet filters and academic freedom : librarian and stakeholder perceptions and their impact on access to information - Orenstein, David I. (2021)
Background. Filtering software is used in libraries to block Web-based content; this includes parts or all of certain websites, ranges of IP addresses, as well as key word level sifting of search results that delete or do not return all possible and alternative content. There are academic institutions that actively do filter access to the Internet for their students, faculty and staff. Objective. How do librarians and other key campus stakeholders view the use of Internet filters? The data presented in this paper comes from a cross-institutional study which surveyed senior administrators, IT professionals, faculty and librarians to gauge their views related to use of Internet filters. Methods. The data selected for this article focuses on a comparative analysis of responses to questionnaires completed by both librarians and senior administrators. However, other outcome data will be discussed for all participant groups. Results. Results suggest that while librarians as a professional group stand firmly for open access and against filters, academic administrators are split on the role filters play in denying access to Internet content. While faculty and IT staff each view the necessity and value of filters with varying degree of approval. Significance. These perceptions have policy implications related to academic freedom for teaching, learning and for academic libraries and IT departments, as well as their parent institutions.